Muscle fiber hypertrophy vs. hyperplasia - Antonio, J.
One of the fundamental questions in exercise physiology has been the mechanism of muscle adaptation to increased force demands (i.e. strength training). The simple and generally correct answer remains that muscles grow in size due to the growth of existing muscle fibers. However, under extreme conditions of muscle size and workload, there is substantial evidence that muscles can take advantage of a more spectacular mechanism; they can split to form additional new fibers, a mechanism termed hyperplasia.